Deposit velocity and its significance - Garvy, George (New York: Federal Reserve Bank of New York, 1959)
This book is one of a series published by the Federal Reserve Bank of New York in order to furnish the student of money and banking with information not readily available elsewhere, concerning monetary policies, institutions, and techniques. It discusses the behavior of deposit velocity, over the business cycle and over longer periods with emphasis on the institutional and structural forces determining this behavior.
Includes bibliographical references.
usc 02/10/2018
Loans
Keywords: Bank deposits; Circular velocity of money; United States